1 Healthtec birmingham – a unique approach to delivering the school curriculum through simulation of careers in the health and care sector. (17th November 2016) - Mansfield, A; Shah, J; Dalton, C
Abstract : HealthTec is a partnership between schools, colleges and employers to make all areas of the curriculum relevant to careers within health, care and science. The project is based in a bespoke simulation centre in The Baverstock Academy in Druids Heath, one of the most deprived areas of Birmingham. The facility was pump-primed by Health Education West Midlands, becoming operational in May 2014 and having since worked with over 8, 000 young people across the region. The key focus of HealthTec is to deliver interactive, simulated experience of jobs and career roles in the NHS, linked to key aspects of the educational curriculum, in order to: Raise awareness of the whole spectrum of careers within the NHS, and encourage students to aspire towards them. Make learners aware of the range of educational pathways they can use to reach these roles. Re-emphasise the link between education and employment. In the pursuit of these aims, HealthTec has worked to bring together health professionals from the public and private sectors, with learners from schools, colleges and universities across the West Midlands. This learning takes place within bespoke simulation scenarios, designed by HealthTec in partnership with specialists from both the education and health sectors. These scenarios have ranged from English departments engaging in a simulated train crash as part of a creative writing assignment, to Geography groups using a replicated disease outbreak to look at movement across borders in a globalised world. HealthTec is now developing a range of unique partnerships with organisations such as the University of Birmingham, to develop this approach and widen participation within the health and care sectors among young people from socially deprived backgrounds. Furthermore, partnerships have been developed with organisations such as the Royal Society for Public Health, to look at innovative ways of delivering qualifications through simulated learning.